2006
DOI: 10.1017/s0014479706003863
|View full text |Cite
|
Sign up to set email alerts
|

Crop Productivity and Land-Use Efficiency of a Teff/Faba Bean Mixed Cropping System in a Tropical Highland Environment

Abstract: Mixed cropping of teff (Eragrostis tef ) with faba bean (Vicia faba) was compared with sole cropping in the 2002 and 2003 growing seasons at Holetta Research Centre, in the central highlands of Ethiopia. The treatments were sole teff (25 kg seed ha −1 ), sole faba bean (200 kg seed ha −1 ) and 12.5, 25, 37.5, 50 and 62.5 % of the sole seed rate of faba bean mixed with a full teff seed rate. A randomized complete block design replicated four times was used. Treatment effects were significant for seed and biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Furthermore, the faba bean plant height increased within the sole plot. This is in agreement with the report of Getachew Agegnehu et al, 2006, which reported sole height of teff were the shortest in the sole plot than the mixtures in a tropical highland environment of Ethiopia.…”
Section: Table 3 Effect Of Intercropping Systems On Yield and Other supporting
confidence: 93%
“…Furthermore, the faba bean plant height increased within the sole plot. This is in agreement with the report of Getachew Agegnehu et al, 2006, which reported sole height of teff were the shortest in the sole plot than the mixtures in a tropical highland environment of Ethiopia.…”
Section: Table 3 Effect Of Intercropping Systems On Yield and Other supporting
confidence: 93%
“…Achieving sustainable supplies of teff flour for immigrant communities, industries (health and baby food), and local residents requires producing the crop locally rather than obtaining it by the less reliable imports (6). Teff is a potential rotation crop in certain environments where rotational crops (1) and late summer feed are limited (35).…”
Section: Teff Is Becoming An Important Crop In the United Statesmentioning
confidence: 99%
“…In addition, intercropping ensures (i) availability of balanced diet to the farmers/locals, (ii) reduces the risks of crop failure due to adverse effects of pests/climate, (iii) lesser manure inputs and sustainability of soil nitrogen resources, (iv) improved use of scarce resources, (v) least soil erosion by providing continuous cover and (vi) also likely increase yield stability, thus providing improved returns (Willey 1979, Jensen 1996, Anil et al 1998, Dapaah et al 2003, Agegnehu et al 2006a, Langat et al 2006). In Himalaya, major inter crop combinations traditionally practiced include cereals with millets, millets with legumes, and legumes with legumes (Maikhuri et al 1997, Singh et al 1997, Nautiyal et al 2002.…”
Section: Discussionmentioning
confidence: 99%